Solve this equation.

`x + 5*sqrt(x) - 36 = 0`

### 1 Answer | Add Yours

The equation `x + 5*sqrt x - 36 = 0` has to be solved.

`x + 5*sqrt x - 36 = 0`

Let `sqrt x = y`

=> `y^2 + 5y - 36 = 0`

=> `y^2 + 9y - 4y - 36 = 0`

=> `y(y + 9) - 4(y + 9) = 0`

=> `(y - 4)(y + 9) = 0`

=> y = 4 and y = -9

y = 4

=> `sqrt x = 4`

=> x = 16

y = -9

=> `sqrt x = -9`

=> x = 81

**The solution of the equation are x = 16 and x = 81**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes